Factors Causing Wives Not Fulfilling Obligations Towards Husbands in the Household (An Analysis of the Impact of Domestic Disharmony in the KUA of Syiah Kuala District): Faktor Penyebab Isteri Tidak Memenuhi Kewajiban Terhadap Suami Dalam Rumah Tangga (Analisis Terhadap Dampak Ketidakharmonisan Dalam Rumah Tangga di KUA Kecamatan Syiah Kuala) - Alidar, EMK; Rispalman, Rispalman; Maisarah, Riska (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2022)
All couples expect a harmonious family or sakinah mawadah warahmah. Ideally to create a household that is sakinah mawadah and warohmah needed a uniform understanding of the rights and obligations between husband and wife. Husband and wife must always carry out their respective obligations in the household. But differently what happened in Syiah Kuala Subdistrict is that the wife did not fulfill her obligations to her husband in the household. In Islamic law, wives should carry out their obligations to serve their husbands, but what happens in Syiah Kuala Subdistrict is that many wives neglect their obligations. This kind of wife is called nusyuz. The problem that wants to be examined in this study is the first, whether the factors that cause the wife not to fulfill the obligation to the husband in the household in Syiah Kuala Subdistrict, the second, how is the impact and legal consequences for wives who do not fulfill their obligations to husbands in the household in Syiah Kuala Subdistrict. This research uses a case approach (Case Approach) which is to examine cases related to issues in the field. The results in this study do not meanthat the factors that cause the wife not to fulfill her obligations to the husband in Syiah Kuala subdistrict are economic pressure factors, career factors, harmony factors of spousal relationships, and domestic violence factors. As for the impact that occurs in the field for wives who nusyuz ini is, there is commotion or domestic violence (Domestic Violence), Infidelity, Hated and not dipeayaihusband, and divorce. Then in Islam the legal consequences for the wife who does not fulfill the obligations to her husband ialah become a wife who disobeys or nusyuz towards the husband. In addition, wives like this also do not deserve aliving from the husband.